A multibiomarker approach to explore interactive effects of propranolol and fluoxetine in marine mussels. (October 2015) - Franzellitti, Silvia; Buratti, Sara; Du, Bowen; Haddad, Samuel P.; Chambliss, C. Kevin; Brooks, Bryan W.; Fabbri, Elena
Abstract: A multi-biomarker approach, including several lysosomal parameters, activity and mRNA expression of antioxidant enzymes, and DNA damage, was employed to investigate the nominal effects of 0.3 ng/L fluoxetine (FX) and 0.3 ng/L propranolol (PROP) alone or in combination (0.3 ng/L FX + 0.3 ng/L PROP) on Mediterranean mussels after a 7 day treatment. FX co-exposure appears to facilitate PROP bioaccumulation because PROP only accumulated in digestive gland of FX + PROP treated mussels. Lysosomal parameters were significantly impaired by FX + PROP treatment, while no clear antioxidant responses at the catalytic and transcriptional levels were observed. Biomarker responses led to a "medium stress level" diagnosis in FX + PROP treated mussels, according to the Expert System, whereas 0.3 ng/L PROP or FX alone did not induce consistent stress conditions. These findings suggest vulnerability of coastal marine mussels to FX and PROP contamination at environmentally relevant levels. Graphical abstract: Highlights: FX and PROP combined effects were assessed in marine mussels using biomarkers. PROP bioaccumulation was observed in digestive gland of FX + PROP treated mussels. Lysosomal parameters were significantly impaired by FX + PROP treatment. No clear antioxidant responses at the catalytic and mRNA levels were observed. FX + PROP treatment increased stress levels of mussels compared with the single chemicals. Abstract : Fluoxetine and propranolol induce interactive effects on marine mussels biomarker responses and pharmaceutical bioaccumulation.